Relation of fish size with that of its otolith in pama croaker, Otolithoides pama (Hamilton, 1822) from Narmada estuary: Fish size - otolith relation of O. pama - Bhakta, Dibakar; Kamble, Suhas Prakash; Meetei, Wakamban Anand; Solanki, Jayesh Kumar; Sah, Rajesh Kumar; Solanki, Sonia; Das, Basanta Kumar (Journal of the Inland Fisheries Society of India, 2023)
The relation of fish size and its otolith was established for pama croaker, Otolithoides pama (Hamilton, 1822). Fish specimens were collected from the bag net catch from the Narmada estuary, India for a period of 8 months (November 2018 to June 2019). The sagittal otoliths were extracted, cleaned, measured, and photographed to comprehend the correlation between fish and otolith size. Each specimen’s otolith length, width, and weight were measured to the nearest size and weight of 0.01 mm and 0.01 g, respectively. The observed length and weight of the fish were in the range of 85 to 288 mm (175.79±33.13 mm) and 3.0 to 186.56 g (43.68±27.67 g), respectively. The recorded otolith length, breadth, and weight were in the range of 2.65 to 12.54 mm (7.20±1.77 mm), 2.01-10.48 mm (5.95±1.33 mm), and 0.02 g to 0.75 g (0.23±0.11 g), respectively. The data for the OL, OB, OW, fish length and weight fitted the power model adequately. Fish length and otolith weight (R2 = 0.931), fish length and otolith breadth (R2 = 0.985), fish weight and otolith length (R2 = 0.942), fish weight and otolith weight (R2 = 0.922), and fish weight and otolith breadth (R2 = 0.962) all had high values for the coefficient of determination. The study also showed a strong relationship between fish size and otolith dimensions. The stock profile of the studied species can be geographically mapped using the results of the current study.